MicroRNA-Assisted Hormone Cell Signaling in Colorectal Cancer Resistance - Crescenzo Massaro; Elham Safadeh; Giulia Sgueglia; Hendrik G. Stunnenberg; Lucia Altucci; Carmela Dell’Aversana (Cells, 2020)
Despite substantial progress in cancer therapy, colorectal cancer (CRC) is still the third leading cause of cancer death worldwide, mainly due to the acquisition of resistance and disease recurrence in patients. Growing evidence indicates that deregulation of hormone signaling pathways and their cross-talk with other signaling cascades inside CRC cells may have an impact on therapy resistance. MicroRNAs (miRNAs) are small conserved non-coding RNAs thatfunction as negative regulators in many gene expression processes. Key studies have identified miRNA alterations in cancer progression and drug resistance. In this review, we provide a comprehensive overview and assessment of miRNAs role in hormone signaling pathways in CRC drug resistance and their potential as future targets for overcoming resistance to treatment.